2009
DOI: 10.1109/map.2009.5162019
|View full text |Cite
|
Sign up to set email alerts
|

CPW-Fed Quasi-Magnetic Printed Antenna for Ultra-Wideband Applications

Abstract: An optimized coplanar-waveguide-fed quasi-magnetic printed antenna for ultra-wideband applications is described. A parameter study, motivated by a design procedure, allowed a substantial increase in the return-loss operational bandwidth. The numerically predicted performance was validated by means of physical measurements of fabricated samples. The measured radiation patterns of the antenna demonstrated its adequate radiation characteristics. The feed radiation was also investigated by means of physical measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The width of the feeding line (W f ) is chosen as 3.56 mm to obtain a 50 Ω characteristic line impedance. The other dimensions are determined by means of bottom-to-up strategy whose main purpose is to improve the impedance matching and its operation steps are summarized as follow [23][24][25]. Firstly, the overall dimensions of the antenna are fixed, then the structure is divided into separate sections ordered by starting from the feeding.…”
Section: Antenna Designs Results and Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The width of the feeding line (W f ) is chosen as 3.56 mm to obtain a 50 Ω characteristic line impedance. The other dimensions are determined by means of bottom-to-up strategy whose main purpose is to improve the impedance matching and its operation steps are summarized as follow [23][24][25]. Firstly, the overall dimensions of the antenna are fixed, then the structure is divided into separate sections ordered by starting from the feeding.…”
Section: Antenna Designs Results and Comparisonsmentioning
confidence: 99%
“…Therefore, the antenna geometry shown in Figure 1(a) is divided into three design sections, two tapered transitions and a radiator, and the resulting antenna is called preliminary PPMA. Two tapered transition sections provide smooth impedance transition between the feeding line and radiation section [23,24]. The first tapered transition section, which is the one adjacent to the feed line, is the most sensitive part, and therefore, this section must be optimized first to get desired impedance bandwidth.…”
Section: Antenna Designs Results and Comparisonsmentioning
confidence: 99%
“…cit. ; Schantz et al, 2003Schantz et al, , 2004and Tanyer et al 2009a), to keep this chapter self-content and avoid cross-reference, we summarize them here:…”
Section: Electric and Magnetic Antennasmentioning
confidence: 99%
“…This antenna was previously discussed in [3,4], the therein presented design methodologies being now stretched to their extreme limits. The result is a printed antenna having an impedance matching bandwidth that, to the authors' best knowledge, exceeds any currently reported performance of similarly fabricated radiators.…”
Section: Introductionmentioning
confidence: 99%
“…The result is a printed antenna having an impedance matching bandwidth that, to the authors' best knowledge, exceeds any currently reported performance of similarly fabricated radiators. Upon recognizing the major impact of the feeding technique on the overall antenna characteristics, a coplanar waveguide (CPW) line is used to this end, the benefits of this solution being extensively examined in [3,4] and the therein cited references. In particular, [4] clearly demonstrated that the radiation from the CPW line has a negligible aport in the global economy of the radiation from this type of antenna, a fact that further recommends such a feeding technique.…”
Section: Introductionmentioning
confidence: 99%